Pemodelan Proses Bisnis Menggunakan IDEF0 Pada Perusahaan Aegipix 3D Studio - Graha Prakarsa; Vani Maharani Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Aegipix 3D Studio is a company engaged in services to create architectural visualizations for architects, interior designers, property developers, marketing agents, housing agents, and landscape planners. Business processes are a very important function for Aegipix 3D Studio companies to work on projects that are accepted. Therefore it is necessary to analyze the performance of each process in the business process, for a development using Business Process Reengineering problem solving methods and business process modeling using IDEF0 modeling, it is expected to speed up the acceptance process (A1) and project work processes (A2 ) which was previously blocked. Especially in the process of working on the project, it is expected to minimize the workmanship due to disruption of scheduling in making the project timeline that has been determined.